2006
DOI: 10.4025/actasciagron.v28i3.964
|View full text |Cite
|
Sign up to set email alerts
|

Atuação de rizóbios com rizobactéria promotora de crescimento em plantas na cultura do caupi (<em>Vigna unguiculata</em> [L.] Walp.)

Abstract: RESUMO.O objetivo deste estudo foi verificar a potencialidade da colonização conjunta em feijão caupi (Vigna unguiculata [L.] Walp.) por Paenibacillus e Bradyrhizobium em diferentes métodos de inoculação que proporcionam crescimento visando a uma agricultura sustentável. Os trabalhos foram realizados na Empresa Pernambucana de Pesquisa Agropecuária (IPA), com Argissolo Amarelo (Itapirema, Estado de Pernambuico), dois modos de inoculação (semente e solo) em cultivar de caupi (IPA-205). Foi determinado: número e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
(1 reference statement)
0
10
0
5
Order By: Relevance
“…During the past couple of decades, the use of plant growth promoting rhizobacteria (PGPR) for sustainable agriculture has increased tremendously in various parts of the world. Significant increases in growth and yield of agronomically important crops in response to inoculation with PGPR have been repeatedly reported (Kloepper et al 1980;Seldin et al 1984;Chen et al 1994;Zhang et al 1996;Amara and Dahdoh 1997;Chanway 1998;Pan et al 1999;Bin et al 2000;Gupta et al 2000;Biswas et al 2000;Mariano and Kloepper 2000;Asghar et al 2002;Vessey 2003;Gray and Smith 2005;Silva et al 2006;Figueiredo et al 2008;Araújo 2008). Studies have also shown that the growth-promoting ability of some bacteria may be highly specific to certain plant species, cultivar and genotype (Bashan 1998;Gupta et al 2000;Lucy et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past couple of decades, the use of plant growth promoting rhizobacteria (PGPR) for sustainable agriculture has increased tremendously in various parts of the world. Significant increases in growth and yield of agronomically important crops in response to inoculation with PGPR have been repeatedly reported (Kloepper et al 1980;Seldin et al 1984;Chen et al 1994;Zhang et al 1996;Amara and Dahdoh 1997;Chanway 1998;Pan et al 1999;Bin et al 2000;Gupta et al 2000;Biswas et al 2000;Mariano and Kloepper 2000;Asghar et al 2002;Vessey 2003;Gray and Smith 2005;Silva et al 2006;Figueiredo et al 2008;Araújo 2008). Studies have also shown that the growth-promoting ability of some bacteria may be highly specific to certain plant species, cultivar and genotype (Bashan 1998;Gupta et al 2000;Lucy et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Coinoculation studies with PGPR and Rhizobia have shown increased plant nodulation and N fixation (Li and Alexander 1988;Araújo and Hungria 1999;Vessey and Buss 2002;Silva et al 2006;Figueiredo et al 2007). Coinoculation of some Bacillus strains with effective Bradyrhizobium resulted in enhanced nodulation and plant growth of green gram (Vigna radiata L.) (Sindhu et al 2002).…”
Section: Coinoculation Of Pgpr and Rhizobia: Improving Nodulationmentioning
confidence: 99%
“…PGPR therefore, also aimed to investigate in relation to available plant essential nutrient in soil (Freitas et al 2007). Significant increase in growth and yield of important crops in response to inoculation with PGPR have been repeatedly reported (Kloepper et al 1980;Chen et al 1994;Zhang et al 1996;Amara and Dahdoh 1997;Pan et al 1999;Gupta et al 2000;Mariano and Kloepper 2000;Asghar et al 2002;Vessey 2003;Gray and Smith 2005;Silva et al 2006;de Araujo 2008). On the other hand, bacteria in the genera Bacillus, Streptomyces, Pseudomonas, Burkholderia, and Agrobacterium are the biological control agents suppress plant disease through production of antibiotics, enzymes and/or siderophores and ISR Uppal et al 2008).…”
Section: Microbial Diversity In Agricultural Benefitsmentioning
confidence: 99%
“…Significant increases in growth and yield of agronomically important crops in response to inoculation with PGPR have been reported many times (Kloepper et al, 1980;Chen et al, 1994;Zhang et al, 1996;Amara and Dahdoh, 1997;Chanway, 1998;Pan et al, 1999;Bin et al, 2000;Biswas et al, 2000;Asghar et al, 2002;Vessey, 2003;Silva et al, 2006). PGPR beneficial effects have been exploited in many areas including biofertilizers, microbial rhizoremediation and biopesticides (Adesemoye et al, 2008) …”
Section: Plant Growth-promoting Rhizobacteria (Pgpr)mentioning
confidence: 99%